2019
DOI: 10.1097/gox.0000000000002003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vascularized Lymph Node Transfer for Extremity Lymphedema Using Volumetric and Circumferential Differences

Abstract: Background:Circumferential difference of lymphedematous limbs at designated anatomic distances has been the primary mode for measuring lymphedematous extremities. Computed tomography (CT) imaging produces accurate, consistent, hygienic volume measurements and a direct limb representation. This study compares these 2 main modalities and assesses their correlation.Methods:CT and circumferential difference measurements, costs, and correlation of patient limbs that received vascularized lymph node transfer were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Although the limb circumferential measurements are a useful tool for monitoring the progress of the lymphedematous limb, improving communication between medical personnel and patients, there have been several critiques against this method for not providing an accurate assessment of volume. However, in a recent study circumferential and CT measurements have been demonstrated being highly complementary …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the limb circumferential measurements are a useful tool for monitoring the progress of the lymphedematous limb, improving communication between medical personnel and patients, there have been several critiques against this method for not providing an accurate assessment of volume. However, in a recent study circumferential and CT measurements have been demonstrated being highly complementary …”
Section: Discussionmentioning
confidence: 99%
“…A standardized CT volumetric protocol was used by our Radiology Department from 2002 and performed for all patients with extremity lymphedema preoperatively and 1‐year postoperatively . CT imaging was performed to provide a more consistent and standardized method to measure the volume of the lower extremity lymphedema from the ankle joint to the level of iliac bone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several critiques have been moved against this tool for not allowing a precise assessment of limb volume. Conversely, a study showed that circumferential and CT measurements are highly complementary in the assessment of volume in the lymphedematous limb [ 29 ].…”
Section: Diagnosis Of Bcrl and Clinical Symptomsmentioning
confidence: 99%
“…CT can detect lymphedema features including skin thickening, honeycombing or presence of fat lobules. It provides a standardized and reproducible method to measure the limb volume providing a 3-D representation of the lymphedematous limb [ 29 ].…”
Section: Diagnosis Of Bcrl and Clinical Symptomsmentioning
confidence: 99%